Characterizing income distribution for poverty and inequality analysis - Chumacero, Rómulo; Paredes, Ricardo (Estudios de Economía, 2016)
This paper presents a systematic empirical characterization of income distribution in Chile. Such characterization helps us to understand the apparent paradox regarding the coexistence of a successful economic performance and persistently high inequality in income distribution and to assess the impact of different social policies dealing with poverty. Segmented sectors seem to be a crucial feature that is generally overlooked in the traditional analysis of income distribution and poverty. As an example, we conduct an exercises to evaluate two types of policies used to alleviate poverty: one focused on increasing coverage of education (wrongly assuming two populations).